Working in groups for coursework assignments : the tertiary students’ perspective - Mustafa, Rosnah; Pung, Wun Chiew; Michael Slee, Shirley (Issues in Language Studies, 2013)
The study examined undergraduates’ perception of group work in doing coursework assignments. It specifically investigated students’ perceptions of the usefulness of group work in doing assignments; identified reasons which influence students’ preference or non-preference for group work in doing assignments; determined students’ expectations of instructor’s roles in group work; and compared students’ perceptions of group work across ethnic groups. A 39-item questionnaire was distributed to 200 students in a Malaysian public university. The findings showed that a majority of students viewed group work positively due to lesser time required to accomplish given tasks and increased interpersonal gains. Some students however disapproved of group work for several reasons including the difficulty to find mutually agreed time for discussions, domination of some group members, and the existence of slackers in the group. One major aspect highlighted in the study was students' need for continuous instructor support and assistance when group work was assigned.